Pengaruh Penambahan Bonggol Nanas Pada Susu Kacang Hijau - Anisa Auliya; Ardia Tita Kartika; Lydea Eftiwin; Istiana Istiana; Sopiah Sopiah; Nurlia Latipah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
The present study utilizes pineapple weevil waste with the aim of testing the durability and flavor of the formulation between pineapple weevil milk bean. Pineapple cob which is one of the abundant waste in Indonesia and has not been used optimally turns out to have nutritional content and bromelain compounds that have many benefits for health, not only that pineapple hump is also useful for preventing cancer and sinusitis. The combination of pineapple green beans in milk making is one of the efforts to improve nutrition in it. In general, this study aims to determine the durability of shelf life and the taste of pineapple (sunggoku) green bean hump milk. This research consisted of two methods, namely an experiment to test the storability of milk and a survey with 28 testers for milk taste.